Inferring Transactions from Financial Statements* - ARYA, ANIL; FELLINGHAM, JOHN C.; GLOVER, JONATHAN C.; SCHROEDER, DOUGLAS A.; STRANG, GILBERT (Contemporary Accounting Research, 2000)
Abstract In this paper, we embed the double entry accounting structure in a simple belief revision (estimation) problem. We ask the following question: Presented with a set of financial statements (and priors), what is the reader's “best guess” of the underlying transactions that generated these statements? Two properties of accounting information facilitate a particularly simple closed form solution to this estimation problem. First, accounting information is the outcome of a linear aggregation process. Second, the aggregation rule is double entry.